David Busch's Canon EOS R10 guide to digital photography - Busch, David D. (Rocky Nook, Inc., 2023)
David Busch's Canon EOS R10 Guide to Digital Photography is your all-in-one comprehensive resource and reference for the highly-affordable APS-C format Canon EOS R10. Beginners and budding enthusiasts alike will appreciate this 24-megapixel camera’s action-friendly 23 frames-per second continuous shooting capabilities. Image stabilization built into many RF-mount lenses – including two all-new RF-S optics introduced with the camera – virtually eliminates blur from camera shake at slow shutter speeds. Three available adapters make it easy to supplement your RF-mount lenses with a broad selection of legacy Canon EF and EF-S lenses. The R10 has wireless connectivity to computers and smart devices and high-definition 4K and Full HD movie-making capabilities. With this book in hand, you can quickly apply all these advanced features to your digital photography, while boosting your creativity to take great photographs with your Canon EOS R10. Filled with detailed how-to steps and full-color illustrations, David Busch's Canon EOS R10 Guide to Digital Photography covers all this upscale camera's features in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included is the handy "roadmap" chapter, an easy-to-use visual guide to the cameras' features and controls. Learn when to use each option and, more importantly, when not to use them, by following the author’s recommended settings for every menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera’s capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Canon EOS R10.